Cross-sectoral coordination failure: How significant a constraint in national efforts to tackle malnutrition in Africa? - Benson, Todd (SAGE Publications, 2007)
Background. Malnutrition arises from multifaceted causes and requires action from multiple sectors to address. Consequently, oversight and direction are said to be required to ensure that public goods and services needed to reduce malnutrition are delivered by the sectors responsible in a coordinated fashion. To do so, many countries have established cross-sectoral national nutrition coordination agencies. Objective. The performance of such agencies established recently in three African countries is evaluated to determine how critical their intersectoral coordination function is to national public efforts to reduce malnutrition. Methods. This evaluation uses qualitative information on the national institutional frameworks within which nutrition activities are carried out in Mozambique, Nigeria, and Uganda, countries with such agencies, and in Ghana, which has none. Results. None of the agencies has so far effectively carried out the three functions on which they were evaluated: cross-sectoral coordination, advocacy to sustain political commitment to address malnutrition, and resource mobilization. No cross-sectoral national nutrition initiatives are being implemented. Nutrition does not feature strategically in the master development frameworks in any country. No additional government resources have been mobilized, although international resources have been. Conclusions. The agencies have proven of limited value to the malnourished in these countries. However, cross-sectoral barriers are not the primary reason for this ineffectiveness. Rather, inability to maintain continued political commitment for efforts to address malnutrition—in short, advocacy—is the principal deficiency in performance. Cross-sectoral coordination only becomes important if malnutrition itself is treated as a politically important problem, thereby stimulating action in various sectors.